Analisis Tingkat Kepuasan Siswa Terhadap Penerapan SIPKALI Menggunakan Metode EUCS (Studi Kasus: Siswa Kelas 3 SMK Farmasi Ikasari) - Syahril (Unversitas Muhammadiyah Riau, 2023)
One area of education is information technology. Information technology is very important to the world of education and helps schools in many ways. Schools such as SMK Farmasi Ikasari have information systems that facilitate interns. The method used in my research is the EUCS method where there are 5 variables namely content, accuracy, format, ease of use and timeliness. Data obtained from a sample of 165 respondents using a questionnaire. The level of student satisfaction based on the EUCS variable in using SIPKALI was 0.396 or 3.96% while 60.4% was influenced by other variables not examined. Based on user satisfaction with the use of SIPKALI, there are 4 variables, namely content 62%, format 61%, accuracy 62% and ease of use 59% the indicators of these variables are greater agreement and in the category can be said to be high for these 4 variables and for the variable Timeliness 57%, the indicator for timeliness is also greater. Agree, but in the category of results, the percentage is less, so from this timeliness variable, users still feel dissatisfied with timeliness.